Perbandingan Pengaturan Tindak Pidana Judi Online Sebagai Cybercrime di Indonesia dan Brunei Darussalam - Evan Adriawan Cipta Perwira; Hartiwiningsih Hartiwiningsih; Sulistyanta Sulistyanta (Indonesian Journal of Social Sciences and Humanities, 2026)
The rapid development of information technology has transformed conventional gambling into online gambling, which is characterized by its borderless nature, anonymity, and complex digital infrastructure. This phenomenon presents significant challenges for criminal law enforcement, particularly within the framework of cybercrime. This research aims to analyze and compare the regulation of online gambling offenses in Indonesia and Brunei Darussalam, and to identify constructive legal reforms that may be adopted in Indonesia. The study employs a normative juridical method using statutory, comparative, and conceptual approaches. The findings indicate that Indonesia adopts a total prohibition model, regulating online gambling through the new Penal Code and the Electronic Information and Transactions Law. Despite fulfilling the principle of legality, enforcement faces obstacles related to digital evidence, cross-border servers, encryption systems, and uneven targeting of offenders. Brunei Darussalam also applies a total prohibition approach but within a dual legal system integrating the Common Gaming Houses Act and the Syariah Penal Code Order 2013. The comparative analysis demonstrates that regulatory effectiveness depends not only on the severity of sanctions but also on normative consistency, institutional integration, and preventive strategies. This study concludes that Indonesia requires harmonization of legal provisions, proportional sentencing differentiation, and stronger institutional coordination to effectively combat online gambling as a form of cybercrime.